The Bingo Long traveling all-stars & motor kings [videorecording (DVD)] - Williams, Billy Dee, 1937-; Jones, James Earl; Pryor, Richard, 1940-2005; Brashler, William (Universal Studios, 1976)
A group of independent renegade players travel around the Midwest looking for that big home run while playing baseball in the 1930's Negro League.